Doświadczenia adolescentów chorujących na raka – przegląd tekstów anglojęzycznych - Pluta, Magdalena (Studia Edukacyjne, 2018)
This article is a review of English-language texts on the experiences of adolescents with cancer. The aim of the article is to show the adolescents’ experiences of cancer based on available research. The review of texts includes studies conducted in the phenomenological approach. Selection of the texts based on specific criteria was followed by their analysis. The analysis was of qualitative and inductive character. Separate analytical categories are: difficulties in surviving cancer, strategies for coping with the disease and benefits of being sick, experience of support from the family and medical staff.